Optical simulation approach as a technique to determine the efficiency of ultraviolet germicidal irradiation in surface disinfectant - Lee, Wen Zhe (2023)
The utilization of surface disinfection has gained increased popularity in recent years due to its effectiveness in killing pathogens. Ultraviolet Germicidal Irradiation (UVGI) is preferable as it is more environmentally friendly compared to other methods. In order to maximize the usage of UVGI technology, it is necessary to identify the mechanism and irradiation performance of the UVGI technology. However, most of the paper are using physical approached nowadays to identify the efficiency of UVGI. In this paper, optical simulation approach had been used to investigate the efficiency of ultraviolet C light (UVC) subjected to the power of light source and distance from light source based on direct ray tracing light simulation methods at a fixed spectrum of 254 nm. A sample of SARS-Cov-2 had been selected to go through surface disinfection for 3, 4 and 5 log reduction respectively. The efficiency of the UVGI technology is further discussed based on the required exposure time to reach total dose for the surface disinfection. According to the simulation, the efficiency of the UVGI system decreases as the distance from the light source increases. However, the result might be varying based on the power of light source.